1987
DOI: 10.1111/j.1471-4159.1987.tb02897.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin III: A Potent Inhibitor of Enkephalin‐Degrading Enzymes and an Analgesic Agent

Abstract: Various angiotensins, bradykinins, and related peptides were examined for their inhibitory activity against several enkephalin-degrading enzymes, including an aminopeptidase and a dipeptidyl aminopeptidase, purified from a membrane-bound fraction of monkey brain, and an endopeptidase, purified from the rabbit kidney membrane fraction. Angiotensin derivatives having a basic or neutral amino acid at the N-terminus showed strong inhibition of the aminopeptidase. Dipeptidyl aminopeptidase was inhibited by angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Following the discovery of the neuronal RAS, numerous studies have reported on the implication of AT1R/AT2R agonists on nociception [27,30,33,[68][69][70][71][72][73][74][75][76]. In spite of the high number of studies conducted, literature data remain highly controversial.…”
Section: At1 and At2 Receptor Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the discovery of the neuronal RAS, numerous studies have reported on the implication of AT1R/AT2R agonists on nociception [27,30,33,[68][69][70][71][72][73][74][75][76]. In spite of the high number of studies conducted, literature data remain highly controversial.…”
Section: At1 and At2 Receptor Agonistsmentioning
confidence: 99%
“…In spite of the high number of studies conducted, literature data remain highly controversial. Some publications describe the analgesic activity of AngII, AngIII, or renin on acute pain tests following central (intracerebroventricular [27,69,71,72,76] or intrathecal [33]) administration. These reports proposed different possible mechanisms of action behind the observed effects.…”
Section: At1 and At2 Receptor Agonistsmentioning
confidence: 99%
“…Angiotensin III is the heptapeptide breakdown product of angiotensin II, lacking the aminoterminal asparagic acid. This peptide inhibits the degradation of met‐enkephalin and potentiates its analgesic activity 25…”
Section: Introductionmentioning
confidence: 99%
“…This peptide inhibits the degradation of met-enkephalin and potentiates its analgesic activity. 25 There are two known GPCRs for angiotensin II, AT 1 and AT 2 , and both are connected to inhibitory G i proteins. 26 Angiotensin II has been shown to be involved in tumor angiogenesis, and the pharmacological inhibition of the ACE suppressed vascular endothelial growth factor (VEGF) expression.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin III has been reported to be the most potent inhibitor. 7 The two-step model of the action of hormones on membrane-bound receptors involves partitioning followed by di †usion of the hormone in the membrane.…”
Section: Introductionmentioning
confidence: 99%